Mannose binding lectin gene (MBL2) functional polymorphisms are associated with systemic lupus erythematosus in southern Brazilians. - Sandrin-Garcia, Paula; Brandão, Lucas André Cavalcanti; Coelho, Antônio Victor Campos; Guimarães, Rafael Lima; Pancoto, João Alexandre Trés; Segat, Ludovica; Donadi, Eduardo Antônio; de Lima-Filho, José Luiz; Crovella, Sergio (Hum Immunol, 2011)
Susceptibility to systemic lupus erythematosus (SLE) has been associated with immunologic, environmental, and genetic factors. To uncover a possible association between MBL2 gene polymorphisms and SLE, we analyzed functional polymorphisms in the promoter and first exon of the MBL2 gene in 134 Brazilian SLE patients and 101 healthy controls. Genotype and allele frequencies of MBL2 A/O polymorphism were significantly different between patients and controls, and the O allele was associated with an increased risk of SLE. An association between low mannose binding lectin (MBL) producer combined genotypes and increased risk for SLE was also reported. Furthermore, when stratifying SLE patients according to clinical and laboratory data, an association between the A/O genotype and nephritic disorders and between the X/Y genotype and antiphospholipid syndrome was evident. Combined genotypes responsible for low MBL production were more frequently observed in SLE patients with nephritis. Our results indicate MBL2 polymorphisms as possible risk factors for SLE development and disease-related clinical manifestations.
Keywords: Adolescent; Adult; Aged; Brazil; DNA Mutational Analysis; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Lupus Erythematosus, Systemic; Male; Mannose-Binding Lectin; Middle Aged; Polymorphism, Genetic; Population Groups; Promoter Regions, Genetic